ANALISIS KEPUASAN PELANGGAN TERHADAP KUALITAS PELAYANAN PERUSAHAAN DAERAH AIR MINUM (Studi Pada PDAM Kota Malang) - Rochmah, Siti (Fakultas Ekonomi, UIN Maliki Malang, 2011)
This study aims to determine the level of customer satisfaction to service quality of the Regional Water Company Malang. The research method used in this research is quantitative descriptive with a population of Malang PDAM customers. The sample in this study of 180 respondens taken with the probability sample. Data taken with questionnaires and interviews and using descriptive percentages. The results showed overall customer satisfaction level would include poor service quality that is equal to 62.25%, which means that customers feel less satisfied with the service taps. Elements of customer satisfaction that are less good at, there are 9 categories of Serviceability, delivery systems, service procedures, disciplinary care workers, service personnel responsibilities, personnel service capabilities, service cost reasonableness, cost certainty, and certainty of service schedules. While there are 8 elements of both categories of product quality, service requirements, clarity of frontline employees, speed of service, justice get service, politeness and friendliness of staff, comfortable environment, and environmental security. Because customer satisfaction is a comparison between expectations and actual performance it is recommended to the taps to increase the service element that has not met customer expectations or the category of poor service and conduct regular research to determine customer satisfaction on the quality of services provided and research results need to be evaluated and followed up.